Stein and Hemingway the story of a turbulent friendship - Larsen, Lyle (McFarland & Co., Publishers, 2011)
"This text explores Gertrude Stein's and Ernest Hemingway's friendship, one of the most fascinating and instructive literary associations of the twentieth century. They moved from a mentor/student relationship to a rivalry between artistic peers. Despite fluctuations--of love, jealousy, resentment and name-calling--their association endured due to Stein's weakness for Hemingway and his need for her"--Provided by publisher.